112-μJ 180-fs Pulses at 1-kHz Repetition Rate From Yb-Doped Laser Based on Strictly All-Fiber CPA Structure - Decai Deng; Haitao Zhang; Qihang Gong; Linlu He; Jiaqi Zu (IEEE Photonics Journal)
In this paper, we reported an Yb-doped, femtosecond, chirped pulse amplification laser based on strictly all-fiber structure. It operated at a low repetition rate of 1 kHz and adopted the synchronously pumping technology to suppress ASE and heat accumulation. A chirped fiber Bragg grating providing adjustable dispersion is used as the pulse stretcher. High order dispersion induced by fiber, grating pair in the system was compensated accurately. Laser pulse with duration of 180 fs and energy of 112 μJ has been obtained. In addition, it has a high long-term stability of energy and a good beam quality, corresponding to energy fluctuation of 0.62% in an hour and M2 factor of 1.15, respectively.